Analysing Relationship Between FDI and Economic Progress: Contemplating the Variations of Fiji’s Political Disequilibrium (1983-2013) - Gosai, Sharnit Shalveen (International Finance and Banking, 2024)
Over the years, the relationship between foreign direct investment (FDI) inflows and economic growth has been scrutinised and investigated by many researchers. Such a relationship aims to determine if foreign investment benefits the receiving nation. We have often witnessed that the receiving country does not accomplish the desired infrastructure for which they have received foreign aid. Political instability and corruption have caused dire stress within the nation. This study mainly investigates the direction of FDI flows within the economy of Fiji and how it helps boost Economic Growth from 1983 to 2013. The study also focuses on the early stages of the industrialisation of Fiji. Furthermore, Fiji has faced numerous structural breaks, such as the three coups encountered by the country. Our results show that, even though FDI has a positive long-run relationship with Economic Growth in Fiji, it is also a volatile component when the nation faces numerous political situations stability, and it remains significantly questionable.